Formation of sub-ion scale filamentary force-free structures in the vicinity of reconnection region. (8th April 2016) - Zelenyi, L M; Frank, A G; Artemyev, A V; Petrukovich, A A; Nakamura, R
Abstract: In this paper we review the results of spacecraft observations of current sheets (CSs) of sub-ion spatial scales in the Earth's magnetotail as well as experiments with these structures in laboratory devices. We demonstrate that such sub-ion CSs having a thickness less than the ion gyroradius are usually formed in the vicinity of the magnetic reconnection region and are supported by strong electron currents flowing along magnetic field lines. The magnetic field configuration of sub-ion CSs is close to the force-free configuration, with a strong shear magnetic field component in the CS central region. Spacecraft observations suggest that parallel electron currents are generated by electron beams (pronounced enhancement of the phase space density for electrons with small pitch angles and energies  ∼1–3 keV). We discuss several models describing such force-free sub-ion CSs.